Motor learning in Sport. A short stroll into a (un)familiar world. [Aprendizaje motor en el deporte: Un corto paseo por un mundo (des)conocido]. - Luis Miguel Ruiz (Ramón Cantó Alcaraz, 2015)
It was in 1990 when Quest published an issue about "Usefulness of motor learning research for physical educators". Several scholars tried to give an answer to this question, while motor learning researchers were in favour of this kind of scientific knowledge (Singer, 1990, Magill, 1990) pedagogues were more sceptical (Locke, 1990; Hoffman, 1990). Is it still a question that needs an answer? Does motor learning and expertise research useful for coaches and teachers? To quote J. von Uexkül "perhaps it would be a good idea to give a short stroll into the world of this (un)familiar world". Recently the philosophy of mind and philosophy of sport has begun to focus on sport expertise (Breivik, 2007; Moe, 2005). Today we are witnessing a change of the explanatory model of motor skill acquisition. Computational and computer metaphor is rejected and dynamic, sensorimotor, extended and enactive positions are the fashionable approaches (Araujo, 2013; Aviles et al., 2014; Clark and Chalmers, 2011; Davids, 2015; Froese and Di Paolo, 2011; Noë, 2010). In some cases these positions are coincidences but not in others. All of the researchers are agree upon the need to consider the mutuality of human beings and their surroundings. The computer metaphor, which at the time was the paradigm of any explanation, is now beginning to be seen as an overcome idea(Moe, 2005; Varela, Thompson and Rosch, 2005).